2022
DOI: 10.48550/arxiv.2205.11963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Data-Production Dispositif

Abstract: Machine learning (ML) depends on data to train and verify models. Very often, organizations outsource processes related to data work (i.e., generating and annotating data and evaluating outputs) through business process outsourcing (BPO) companies and crowdsourcing platforms. This paper investigates outsourced ML data work in Latin America by studying three platforms in Venezuela and a BPO in Argentina. We lean on the Foucauldian notion of dispositif to define the data-production dispositif as an ensemble of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The generative AI output companies such as Meta and OpenAI seek to optimize along with other data work only deepens the "precarization, alienation, and surveillance" of data workers (Miceli and Posada, 2022), as their labor, expertise, psyche, and infrastructures are exploited for this optimization. Such practices bear the hallmark of coloniality, but modernity is at play as well, with the West's "selfdelusion that it occupies an epistemic objectivity and thus may treat all other pieces of knowledge and ways of being as expendable peculiarities" (Mumford, 2022).…”
Section: Modernity/colonialitymentioning
confidence: 99%
See 3 more Smart Citations
“…The generative AI output companies such as Meta and OpenAI seek to optimize along with other data work only deepens the "precarization, alienation, and surveillance" of data workers (Miceli and Posada, 2022), as their labor, expertise, psyche, and infrastructures are exploited for this optimization. Such practices bear the hallmark of coloniality, but modernity is at play as well, with the West's "selfdelusion that it occupies an epistemic objectivity and thus may treat all other pieces of knowledge and ways of being as expendable peculiarities" (Mumford, 2022).…”
Section: Modernity/colonialitymentioning
confidence: 99%
“…Through this process, data is turned into a commodity to be bought and sold in the big data marketplace of AI Empire as just another product in the hands of the data brokers responsible for "the Costcoization of data," where acquiring even the most personal data and analyzing it using advanced AI technologies is akin to going to a big-box store to purchase everything you need in one place (Lamdan, 2022). Extractivism does not stop at appropriating data; however, the exploitation of labor, natural resources and effects, and climate degradation are also an inextricable part of this logic (Crawford, 2021;Miceli and Posada, 2022;Sultana, 2022).…”
Section: Extractivismmentioning
confidence: 99%
See 2 more Smart Citations
“…Geva et al [22] recommend that labelers for testing and training datasets be distinct groups since they found that subjective NLP labels produced by a group do not generalize well. Instructions for annotators have also been found to embed bias [47,42]. In the context of face annotation, Engelmann et al [15] argue that 'secondary' (i.e., subjective) characteristics may not be appropriate attributes for facial recognition systems to predict.…”
Section: Bias In Machine Learningmentioning
confidence: 99%